Az 1918-1919. évi háború jellege a magyar történelemben = The 1918-1919 War in Hungarian military history - Nagy, Miklós Mihály (Közép-Európai Közlemények, 2018)
World War I did not end in the fall of 1918 either in Central Europe, nor in the Carpathian Basin. Instead, the war dwindled on in the region for five more years. During the Great War and the years following it, several local wars were fought in the geographical zone taking shape in the center of Europe’s spatial structure. One of these local conflicts was the one in the Carpathian Basin, which can be divided into two phases: the period of the republic led by Mihály Károlyi, and the months of a following far-left dictatorship. The process started on the October 31, 1918, the day the military of the Austro-Hungarian Empire collapsed, and lasted until August 3-4, 1919, when the Romanian military occupation of Budapest occurred. The official Hungarian historiography depicted these events differently before and after 1945. Until the Soviet military occupation of Hungary, these events were described as a military collapse and a “red war”, while after 1945 they were referred to – according to Marxist approach – as a civil-democratic and a socialist revolution. Due to these differing interpretations, which were greatly influenced by political ideologies, one important factor has been overlooked. Hungarian scholars have not yet established clearly whether the internal and external conflicts in the Carpathian Basin were events in a single war, and what the nature of these conflicts was. This study presents the opposing interpretations, discusses Hungary’s isolation regarding foreign affairs that determined the events in these two time periods, and argues that this conflict was in fact a Hungarian patriotic war.